Ultrasonic treatment regulates the properties of gelatin emulsion to obtain high-quality gelatin film - Xin Li; Xiao-Mei Sha; Hong-Shun Yang; Zhong-Yang Ren; Zong-Cai Tu (Food Chemistry: X, 2023)
Gelatin emulsion was an important process for preparing gelatin films. A gelatin film with water resistance and ductility could be prepared using gelatin emulsion, whereas the prepared gelatin film has several defects (e.g., low tensile strength and poor thermal stability). This study aimed to modify gelatin emulsion through ultrasonic treatment, then gelatin film was prepared by the modified gelatin emulsion. The results showed that: under the condition of ultrasonic treatment for 12 min at 400 w, zeta potential and viscosity of gelatin emulsion were the largest; thickness, water vapor permeability (WVP) and water solubility (WS) of corresponding gelatin film were the lowest, and the tensile strength (TS), elongation at break (EAB), denaturation temperature (Tm) and enthalpy value (ΔH) of corresponding gelatin film were the highest. The above result suggested that ultrasonic treatment can be used to prepare a gelatin film with better quality by regulating the properties of gelatin emulsion, and a certain correlation was found between the properties of gelatin emulsion and the properties of gelatin film.